1994
DOI: 10.1182/blood.v83.4.1060.1060
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of minor histocompatibility antigens on lymphocytic and myeloid leukemic cells by cytotoxic T-cell clones

Abstract: Clinical studies indicated an enhanced antileukemic effect of allogeneic bone marrow transplantation (BMT), as compared with autologous BMT. After allogeneic HLA-identical BMT, donor-derived cytotoxic T lymphocytes (CTLs) directed at minor histocompatibility (mH) antigens on the recipients, tissues can be shown. To evaluate the antileukemic reactivity of mH antigen-specific CTLs, we analyzed the expression of mH antigens on circulating lymphocytic and myeloid leukemic cells. We show that the defined mH specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…mHag polymorphism; and 3) restricted tissue distribution. Moreover, since mHag are clearly expressed on circulating leukemic cells and clonogenic leukemic precursor cells of hoth myeloid and lymphoid origin (164,165). hoth types of leukemias can be targeted.…”
Section: Adoptive Immunotherapy Of Leukemiamentioning
confidence: 99%
“…mHag polymorphism; and 3) restricted tissue distribution. Moreover, since mHag are clearly expressed on circulating leukemic cells and clonogenic leukemic precursor cells of hoth myeloid and lymphoid origin (164,165). hoth types of leukemias can be targeted.…”
Section: Adoptive Immunotherapy Of Leukemiamentioning
confidence: 99%
“…In several studies, we have demonstrated that both CD4-and CD8-positive CTL recognizing mH antigens conld be generated in vitro {35, 36,41,42). All mH antigen-specific CD8-positive CTL showed strong lysis of circulating, relatively mature leukemic cells as well as potent antigen-specific cell-mediated suppression or killing of clonogenic leukemic precursor cells (43)(44)(45). Some of the CD4+ clones recognizing mH antigen showed only weak lysis of circulating leukemic cells depending on the density of class II molecules on the cell membrane and the sometimes heterogeneous distribution of class II molecules on the leukemic cell populations (42).…”
Section: Analysis Of Anti-leukemic Reactivity During Clinical Anti-lementioning
confidence: 99%
“…Minor histocompatibility antigen (mHA) differences between patients and their HLA-identical sibling donors are responsible for the alloreactivity causing GVHD and GVL reactions (Barrett & Malkovska, 1996). Leukaemia cells have been shown to express mHAs also present on normal cells (van der Harst et al, 1994). There is some evidence that myeloid leukaemia cells also express two classes of antigen: 'leukaemia-specific' antigens derived from chromosomal translocations, and myeloid-restricted antigens present on leukaemic and normal cells of the myeloid series (Barrett & Malkovska, 1996;Pawelec et al, 1996).…”
Section: Discussionmentioning
confidence: 99%